2001
DOI: 10.2334/josnusd.43.193
|View full text |Cite
|
Sign up to set email alerts
|

Color stability of different denture teeth materials: An in vitro study.

Abstract: Abstract:The value, the filtered coffee, tea, and cola had slight staining effects on all 6 groups of denture teeth. (J. Oral Sci. 43, 193-205, 2001)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
99
1
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(117 citation statements)
references
References 17 publications
12
99
1
5
Order By: Relevance
“…Nonetheless, the effect of staining solutions on darker teeth should be a subject to be further investigated in future studies. For drinks, coffee, tea, and coke are identified to be staining substances 3,7,9,[17][18][19][20] . For this reason, these solutions were used in this study for staining effect evaluation.…”
Section: Teethmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the effect of staining solutions on darker teeth should be a subject to be further investigated in future studies. For drinks, coffee, tea, and coke are identified to be staining substances 3,7,9,[17][18][19][20] . For this reason, these solutions were used in this study for staining effect evaluation.…”
Section: Teethmentioning
confidence: 99%
“…However, if removable dentures were used for a long period of time without sufficient cleaning, there belies too the staining possibility of porcelain teeth because of the adsorption of colorants on the porcelain surface. In dental literature, only a few studies have reported on the color stability of both acrylic and porcelain denture tooth materials [3][4][5] . Against this backdrop of information scarcity, this in vitro study was undertaken to analyze the color changes of porcelain and acrylic denture teeth when exposed to common beverages by means of a spectrophotometer.…”
Section: Introductionmentioning
confidence: 99%
“…According to Mutlu-Sagesen L, et al, [10] less colour stability of acrylic denture teeth could be explained by the water sorption property.…”
Section: Discussionmentioning
confidence: 99%
“…In dental literature, the staining of various aesthetic dental materials like composite resin [1,3-5,7] and maxillofacial silicone [8] by cigarette smoke has been reported,. Also, there is a good amount of literature which have reported staining which was caused by food colourants, like staining of artificial teeth [9,10], aesthetic restorative materials [11,12], denture base resin [13] and acrylic resins for provisional restoration [14]. Some authors had evaluated colour stabilities of denture teeth as was affected by both polymerization methods and thermal cycling [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation